2000
DOI: 10.1046/j.1365-2273.2000.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging results in patients with central electronystagmography findings

Abstract: The objective of this study was to determine the findings on magnetic resonance imaging (MRI) in patients identified as having central vestibular abnormalities on electronystagmography (ENG) testing, to discuss the issue of 'gold standard' in the investigation of central oculo-vestibular system diseases and to present a model for understanding this area. A retrospective review of the case notes of patients (n = 23) found to have central ENG findings at vestibular assessment and for whom MRI scanning data was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…An older study by Stoddart et al . 20 reported that the incidence of structural abnormality identification using MRI in patients with central ENG findings is low. Currently, videonystagmography, video head impulse tests and vestibular evoked myogenic potentials are used for vestibular testing and advances in MRI technology have improved its sensitivity in identifying abnormal white matter lesions compared to CT. 21…”
Section: Discussionmentioning
confidence: 99%
“…An older study by Stoddart et al . 20 reported that the incidence of structural abnormality identification using MRI in patients with central ENG findings is low. Currently, videonystagmography, video head impulse tests and vestibular evoked myogenic potentials are used for vestibular testing and advances in MRI technology have improved its sensitivity in identifying abnormal white matter lesions compared to CT. 21…”
Section: Discussionmentioning
confidence: 99%
“…Of the clinical signs of a central lesion, vertical nystagmus was the only one diagnosed in this population. In terms of ENG findings, the abnormalities indicative of central lesions which were identified in our series were square waves, abnormal saccades in terms of accuracy and a low fixation index in caloric responses 4 . A directional preponderance may be present in both central and peripheral lesions 7 .…”
Section: Methodsmentioning
confidence: 48%
“…Firstly, MRI was performed in all patients with a diagnostic dilemma, not just those with previous abnormal ENG findings suggestive of a central lesion. This methodological difference may be crucial in enabling identification of patients with central lesions who may otherwise escape diagnosis because they have undergone only ENG 4 , 5 . In addition, through this procedure, one may estimate the number of patients with functional abnormalities of the vestibulo-ocular system which have escaped MRI diagnosis, either because they are peripheral or because they are not presented as detectable, concise, structural lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations